Regional digital economy in the Danube Member States under the impact of the new challenges - Ionescu, Romeo Victor; Zlat, Monica Laura; Antohi, Valentin Marian; Matis, Cosmin Dumitru (Technological and Economic Development of Economy, 2023)
The paper aims to analyse the changing economic structure and the trends of the digitalization amplification through the prism of a dynamic multi-criteria model, assessing the strategic perspective by pivoting digitalization in the strategic equation. The main objectives of the research cover the context of vulnerability across the EUSDR countries, the solutions from the literature review and the definition, testing and implementing of a new dedicated model. The model takes into account regional indicators, reported by Eurostat. Statistical analysis procedures and methods were applied in order to capture the expected disparities under the impact of the pandemic, as well as harmonization with European Strategy for Danube Region (EUSDR) – specific impact indicators. The analysis uses la latest official statistical data from Eurostat. The importance of this scientific approach lies in the fact that the results are applicable to the wider region, the vast majority of the Danube states being EU members (9 states), 3 candidate states and 2 potential candidate states in the new geo-political and military context. States that are not yet EU members have regional and cross-border cooperation agreements with the EU. Moreover, the region itself has reacted in a unified way to the challenges of the economic and pandemic crises, the study being conducted over the period 2004–2020. In addition, EU Member States have additionally benefited from European emergency allocations to counter the effects of the global economic crisis and stem the spread of the pandemic. We used empirical and analytical methods, starting with the study of literature, data collection and consolidation of the database, its homogeneity and the application of modelling procedures. The major key findings are focused on the existence of a strong connection between investment effort, labour skills, sustainable development and the digital economy able to face new global and regional challenges. The policy implication of this research consist in offering viable elements capable of assisting regional decision-makers in adopting topical measures on digitisation and reconfiguring strategic regional connections to maintain a sustainable direction for the EUSDR. The recommendations from this study imbraca forma some directions for action related to labour high skills, digitalization, R&D investment and e-commerce.First published online 22 November 2022